The Politics of Economic Regionalism - Cai, K. author. aut Link
XIII, 196 p.
Keywords: While major theories of economic regionalism in the existing literature are primarily constructed to explore institutionalized regional integration, European integration in particular, the analytical framework developed in this work explains the unique process and pattern of regional integration in East Asia.